Understanding of Nidāna w.s.r. to Nidāna Sthāna of Caraka Saṃhitā- A Conceptual Study. - Sandeep; Sonkar, Satyam; Gupta, Piyush; Kumar, Saurabh (International Research Journal of Ayurveda & Yoga, 2023)
On the basis of Dosha, Dushya, Srotas, Agni etc. (Āyurvedic tools for diagnosis) we can make out the disease as well as management. As per ancient Āyurvedic scholars there may not be the nomenclatures of all the diseases in transcript but these all can be managed on the basis of Doshika (pathological) concern. A disease is caused due to specific causative factors followed by the pathogenesis with the manifestation of sign and symptoms and if ignored the complication is the next outcome. Caraka has stated that the diagnosis is very important and essential before proceeding to medicine prescription. Āyurvedic way of diagnosis has two basic components namely ‘Roga Pariksha’ and ‘Rogi Pariksha’, which refers to Examination of disease and Examination of patient respectively. Among them Roga Pariksha gives us the detailed knowledge about a disease starting from the etiological aspects to the actual manifestation of disease. All three Brihatrayis mention Nidana Sthana but the explanation of Nidana Panchaka, Nidanarthakara Roga, Utpatti of diseases etc. were first given in Caraka Nidana Sthana. The five basic components of Roga Pariksha are Nidāna, Purvarupa, Rupa, Upashaya and Samprapti, which are collectively known as ‘Nidāna Panchaka’. Apart from diagnosing a disease, they also play a key role in planning the treatment of that disease. Ācārya Caraka has stated plenty of concepts while describing the eight chapters of Nidāna sthāna. So, in the present study along with the concept of Nidāna, the Nidāna sthāna of Caraka Saṃhita were critically analyzed.